Pengaruh Fasilitas dan Pelayanan terhadap Tingkat Kepuasan Nasabah Bumdes Bucor Wetan Pakuniran Probolinggo - Maryani (Fakultas Ekonomi dan Bisnis Islam, 2020)
BUMDES was born as a new approach in an effort to improve the village economy based on the needs and potential of the village. BUMDES management is fully implemented by the village community, namely from the village, by the village, and for the village. As a business entity engaged in business, certainly in increasing the level of customer satisfaction the need for good services and facilities. If customer satisfaction declines, it is clear that this will be closely related to the next number of customers. The importance of increasing service dimensions and facility dimensions will have a major effect on the satisfaction of BUMDES customers or consumers after becoming a member in it. The results showed that services and facilities had an effect on customer satisfaction at BUMDes Bucor Wetan Village, Pakuniran District, Probolinggo Regency. This shows that the better the services provided and the better the facilities provided, the better the satisfaction felt by the customer